ANAK ANGKAT DALAM PERATURAN DI INDONESIA - usman, munadi (Indonesian Association of Islamic Family Law Lecturers, 2019)
The adoption of children in Indonesia is a long standing tradition with varied motives and goals depending on the customs of the people of a region or those who adopt children. Due to the large number of child adoptions, the government has issued several regulations relating to child adoption in the form of law, government regulation and Ministerial regulation. This study wants to examine the extent to which these regulations have accommodated the rights of adopted children in the family. This research is included in the study of normative law with the aim of analyzing the rules of adoption of children in Indonesia through a human rights approach or in Islam known as maqashid al-shariah.